Assessment of Science Teachers’ Awareness towards Communicable Diseases Control in Baghdad City Primary Schools - Faraj, raad; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To assess of Science Teachers’ Awareness towards Communicable Diseases Control in Baghdad City Primary Schools Methodology: A descriptive study was conducted, included (100) primary school, (50) in Al-Rassafa sector, and (50) in Al-Karkh sector, from March 5th 2012 to March 15th 2013, to assess of science teachers’ awareness towards communicable diseases control. A cluster sample of (100) Science teachers (males and females) were selected, as one teacher from each school. A questionnaire format was used for data collection. The validity of questionnaire was estimated through a penal of experts related to the field of study, and its reliability was estimated through a pilot study conducted in (20) schools (excluded from the original sample) which included (20) teachers from April 8th 2012 to April 14th 2012. Data were analyzed through the application of descriptive and inferential statistical analysis. Results: The results of the study indicated that (78%) of sample were female, and (39%) of them their ages were between (40-49) years old, (65%) of them were married, while (21%) of them were single, and (50%) of them were institute graduates. Also the study indicated that (26%) of teachers had (15–19) years of employment in teaching sector. Furthermore, (58 %) of sample had no opportunity to be involved in training courses concerning communicable diseases control. The results of this study indicate that, teachers’ awareness was poor (in adequate awareness) towards communicable diseases control, immunity and immunization, and also concerning health problems in school. Recommendations: The study recommends that there is a need for cooperation between the Ministry of Health and the Ministry of Education to prepare a textbook for primary schools students about the nature of the communicable diseases and how to control them with adequate explanation of the most important diseases in school provided with photos and illustrations, and emphasis on continuous sessions concerning communicable diseases control for teachers in all primary schools